Bioenergetic Changes Underline Plasticity of Murine Embryonic Stem Cells. (24th January 2019) - Vlaski-Lafarge, Marija; Loncaric, Darija; Perez, Laura; Labat, Véronique; Debeissat, Christelle; Brunet de la Grange, Philippe; Rossignol, Rodrigue; Ivanovic, Zoran; Bœuf, Hélène
Abstract : : Murine embryonic stem cells (mESCs) are endowed by a time-dependent window of plasticity during their early commitment steps. Indeed, while mESCs deprived of leukemia inhibitory factor (LIF) for 24 hours revert to their naive pluripotent state after subsequent LIF readdition, cells deprived of LIF for 48 hours are no longer efficient in reverting, upon LIF addition, and undergo irreversible differentiation. We investigated undisclosed bioenergetic profiles of early mESC-derived committed cells versus their undifferentiated states in order to reveal specific bioenergetic changes associated with mESC plasticity. Multiparametric bioenergetic analysis revealed that pluripotent (+LIF) and reversibly committed cells (−LIF24h) are energetically flexible, depending on both oxidative phosphorylation (OXPHOS) and glycolysis. They exhibit high mitochondrial respiration in the presence of the main energetic substrates and can also rely on glycolysis in the presence of OXPHOS inhibitor. Inhibition of the glycolysis or mitochondrial respiration does not change drastically the expression of pluripotency genes, which remain well expressed. In addition, cells treated with these inhibitors keep their capacity to differentiate efficiently upon embryoid bodies formation. Transition from metabolically active mESCs to irreversibly committed cells is associated with a clear change in mitochondrial network morphology, to an increase of adenosine triphosphate (ATP) produced from glycolysis and a decline of ATP turnover and of the mitochondrial activity without change in the mitochondrial mass. Our study pointed that plasticity window of mESCs is associated with the bivalent energetic metabolism and potency to shift to glycolysis or OXPHOS on demand. LIF removal provokes glycolytic metabolic orientation and consecutive loss of the LIF-dependent reversion of cells to the pluripotent state. Stem Cells 2019;37:463–475 : Abstract : Murine embryonic stem cells, pluripotent with leukemia inhibitory factor (LIF), are induced to differentiate by removing LIF for the times indicated in hours. The metabolic status of cells is indicated along with their properties. The switch toward "glycolysis mainly" status is associated with irreversible LIF-dependent commitment of cells and loss of plasticity during this early time window.